Hydrogen sulfide removal from biogas using chemical absorption technique in packed column reactors - M.B. Kulkarni; P.M. Ghanegaonkar (Global Journal of Environmental Science and Management)
The toxicity and corrosion potential of hydrogen sulfide in raw biogas underlines the need for biogas purification. Several techniques available for removal of hydrogen sulfide from biogas are out of the reach for common end users due to lack of knowledge, higher running costs, and insufficient operational skills. The present experimental study aims to propagate hydrogen sulfide removal techniques amongst the end users by using a low-cost chemical absorption technique and packed column reactors. Commercial grade chemicals like monoethanolamine, sodium hydroxide, calcium hydroxide, granular activated carbon, and steel wool were used for biogas purification in packed column reactors of 1.2 liters capacity. Hydrogen sulfide removal efficiency up to 92.41% was achievable using single purification columns. The efficiency achieved by using multiple purification column was up to 96.84%. Hydrogen sulfide removal efficiency was calculated for experimental variants like the use of a dedicated purification column, multiple purification columns, flow variations and pressure variations of raw biogas. The data for the frequency of regeneration/replacement of different chemicals was also determined. The simplicity of operation and the use of low-cost reagents in the present study can enable the use of these methods amongst end users of biogas technology for minimizing health hazards and corrosion problems.